A Study Of Knowledge Creation In Six Sigma Dmaic Project Success And Its Impact On Organizational Performance - Ang, Boon Sin (2015)

(untitled)
Terdapat banyak penyelidikan empirikal yang mengkaji hubungan antara Six Sigma dan prestasi organisasi. Walau bagaimanapun, kebanyakan penyelidikan ini memberi tumpuan kepada hubungan terus antara Six Sigma dan prestasi organisasi. Tidak ada siasatan terperinci bagaimana Six Sigma boleh menyebabkan peningkatan prestasi organisasi. Kajian ini mencadangkan bahawa dengan mengintegrasikan proses penciptaan pengetahuan organisasi, hubungan antara Six Sigma dan prestasi organisasi dapat dijelaskan dan dibangunkan. Kajian ini mengkaji kewujudan hubungan antara proses penciptaan pengetahuan organisasi dalam projek Six Sigma DMAIC, pengetahuan, Six Sigma kejayaan projek dan prestasi organisasi. There are number of empirical researches that are studying the relationship of Six Sigma and organizational performance. However, most of them are focusing on direct relationship of Six Sigma and organizational performance. There is no detail investigation how Six Sigma can lead to the improved organizational performance. This research suggests that by integrating organizational knowledge creation processes the link between Six Sigma and organizational performance can be explained and developed. This study investigates the existence of a relationship between organizational knowledge creation processes in Six Sigma DMAIC project, knowledge, Six Sigma project success and organizational performance.